Indications and Current Surgical Techniques for Keratoplasty: A 10-year Review from 2011 through 2020 at a Tertiary Referral Hospital in Thailand - Booranapong, Wipawee; Junsangsri, Chayanit; Chirapapaisan, Chareenun; Ngowyutagon, Panotsom; Kengpunpanich, Sathiya (Siriraj Medical Journal, 2025)
Objective: To report the indications and current trends in surgical techniques for keratoplasty over 10 years at Siriraj Hospital. Materials and Methods: We retrospectively reviewed the medical records of hospitalized patients who underwent keratoplasty from 2011 to 2020. The collected data comprised demographics, indications for keratoplasty, and surgical techniques used. Results: A total of 754 eyes were included. Active infectious keratitis was the most common indication (26.1%), followed by bullous keratopathy (20.8%) and regraft (19.2%). There was no significant change in indications for keratoplasty between the first 5-year period and the second 5-year period. Fungal keratitis remained the most common etiology for keratoplasty. Penetrating keratoplasty (PKP) was the most common procedure overall (90.7%), followed by endothelial keratoplasty (EK; 5.7%) and deep anterior lamellar keratoplasty (DALK; 3.6%). However, surgical techniques used in the second 5-year period differed significantly from those in the first 5-year period (P < 0.05). The use of PKP decreased from 96.0% to 86.7%; however, EK increased from 1.5% to 8.9%, while DALK rose slightly from 2.5% to 4.4%. Conclusion: Active infectious keratitis was the most common indication for keratoplasty, followed by bullous keratopathy and regraft. These indications may be reduced through collaborative efforts among government leaders, public health officers, and ophthalmologists. PKP remained the most common surgical technique due to the high incidence of infectious keratitis. However, the use of lamellar keratoplasty, including EK and DALK, significantly increased for other indications. Descemet membrane endothelial keratoplasty was performed mostly in eyes with Fuchs endothelial dystrophy.